Role of different Salmonella enterica serotypes in THP-1 macrophage-derived foam cell autophagy and inflammatory response - Wong, Min Yi; Tseng, Yuan-Hsi; Huang, Tsung-Yu; Chiu, Cheng-Hsun; Chen, Chyi-Liang; Huang, Yao-Kuang (Penerbit Universiti Kebangsaan Malaysia, 2019)
Infected aortic aneurysm is a rare but life-threatening condition. Intimal injury, especially in arteries with atherosclerotic plaques, is vulnerable to Salmonella species. In this study, THP-1 macrophage-derived foam cells were used to mimic the atherosclerotic plaques. We investigated the role of different Salmonella serotype infections in foam cell autophagy and inflammatory response. Three different serotypes of Salmonella enterica-Typhimurium, Enteritidis, and Choleraesuis - with or without a virulence plasmid were used in this study. The foam cell model was established and observed under confocal microscopy. The expression of autophagy and inflammasome-related proteins after Salmonella infection was detected by Western blotting, and the secretion of the proinflammatory cytokines interleukin-1β and IL-18 was detected using ELISA. The plasmid-bearing S. enteritidis OU7130- and plasmid-less S. choleraesuis OU7266-infected foam cells both showed a lower expression of beclin-1 at 0.5 h post-infection (hpi) and p62 at 2 hpi as well as a higher expression of caspase-1 at 2 hpi than other infected cells. Moreover, infection of OU7266 induced the highest IL-1β and IL-18 production among the tested strains. In conclusion, the virulence plasmid of S. enteritidis OU7130 induced foam cell inflammatory responses, whereas that of S. choleraesuis played an opposite role. The different serotype of Salmonella may impact the infected aortic aneurysms through regulating inflammatory balance of the macrophage and foam cells in the atherosclerotic plaque.